2010
DOI: 10.1097/jnr.0b013e3181fc6471
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality, Fatigue, and Related Factors Among Perimenopausal Women in Taipei City

Abstract: It is crucial to assess sleep quality in perimenopausal women who complain of fatigue and/or depression. In addition, health providers should integrate assessments of factors of significant influence on the sleep quality of perimenopausal women (e.g., fatigue; long-term drug, hormone, and/or nutritional supplements use; menopausal status, and tendency toward anxiety and/or depression).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
(16 reference statements)
1
1
0
Order By: Relevance
“…Hung et al [7] and Zhang et al [5] have reported the similar result. As a potential high-risk factor, women with advanced maternal age were more likely affected by physiological and psychological factors [31], thus leading to the deterioration of sleep quality [32].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Hung et al [7] and Zhang et al [5] have reported the similar result. As a potential high-risk factor, women with advanced maternal age were more likely affected by physiological and psychological factors [31], thus leading to the deterioration of sleep quality [32].…”
Section: Discussionsupporting
confidence: 72%
“…What's more, most pregnant women (84%) report sleep disturbances of some severity, and 30% report that they rarely or never get a good night's sleep during pregnancy [4]. A study based on Chinese population showed that 35.8% of pregnant women suffer from sleep disorders [5]. Consequently, poor sleep quality during pregnancy has become a frequent problem threatening pregnant women's health.…”
Section: Introductionmentioning
confidence: 99%